Approximation of bounded functions by positive linear operators - Bustamante, Jorge (Modern Mathematical Methods, 2024)
A general family of positive linear operators associated with a power expansion is studied. An upper estimate of the rate of convergence is obtained for bounded continuous functions in \([0,∞)\) that has limit when \(x→ ∞\). Applications are included.